Characterisation Of The Alkaline Peroxide Pulps From The Oil Palm Empty Fruit Bunch And Their Potential For Cellulose Acetate Production - Kamaludin, Nurul Hasanah (2013)
The first phase of this study involved the making and analyses of hand sheet made from the fibers of the oil palm empty fruit bunches via the process called the alkaline peroxide pulping (APP). This was followed by a two-stage paper recycling process Eight sets of hand sheets were made from the fibers extracted from the varying EFb-alkaline peroxide (AP) reaction duration The pulp and fines from the process were studied and the possibility of incorporating the fines in paper was also assessed. It is noteworthy that the fines collected as materials retained on the 400-mesh screen (R400) could improve hand sheet tensile strength by 100%. Recycling of this pulp, however, showed a declining mechanical properties of hand sheets. This is attributable to fibre hornification and weak inter-fibre bonding as a consequence of re-wetting and repeated disintegration of the hand sheets. Owing to the lost papermaking capacity, pulp purification was therefore attempted to upgrade the pulp to become raw material for cellulose acetate (CA) production. As a result of totally chlorine-free bleaching (TCF) purification of the alkaline peroxide pulp by oxygen-ozone-peroxide (OZP) sequence, CA powders and films show the smoothest oxygen-ozone-peroxide cellulose acetate (OZPCA) film surface produced by incorporation of plasticiser. With or without plasticiser, the produced CAs show thermal characteristics that are similar to those of the commercial CA.